Breaking bad news about transitions to dying: A qualitative exploration of the role of the District Nurse. (February 2015) - Griffiths, Jane; Ewing, Gail; Wilson, Charlotte; Connolly, Michael; Grande, Gunn
Background: UK District Nurses have an important role in enabling a good death. Patients and families need to know the patient is approaching the dying phase, yet evidence suggests breaking bad news about the patient's transition to dying rarely happens. District Nurses spend a lot of time with patients and families during the dying phase and are ideally placed to recognise and discuss the transition to dying. Aim: To explore the role of District Nurses in breaking bad news of transition to dying. Design: Qualitative focus groups. Setting: Primary care (District Nurse service); Four National Health Service Trusts, North West England. Participants: A total of 40 District Nurses across the Trusts, all Registered General Nurse qualified. Median number of years as a District Nurse was 12.5. All had palliative cancer patients on their caseloads. Results: District Nurses' role in breaking bad news of transition to dying was challenging, but the conversation was described as essential preparation for a good death. Four main challenges with the conversations were patients' responses to the prognosis (unawareness, denial and anger), timing the conversation, complexities of the home environment and limited preparation in this aspect of their work. Conclusions: District Nurses are with patients during their last weeks of life. While other colleagues can avoid breaking bad news of transition to dying, District Nurses have no choice if they are to provide optimal end of life care. While ideally placed to carry out this work, it is complex and they are unprepared for it. They urgently need carefully tailored training in this aspect of their work, to enable them to provide optimal end of life care.